DISHARMONY IN THE IMPLEMENTATION OF RELIGIOUS EDUCATION POLICIES FOR INDIGENOUS BELIEF STUDENTS IN INDONESIA - Kurniawan, Muchamad Arif; Ngono, Yves Victor; Rohman, Rohman; Auda, Nurul (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The implementation of religious education policies for students of indigenous beliefs in Indonesia faces challenges in regulation, practice, and social acceptance. This study analyzes the disharmony in policy implementation, focusing on three aspects: (1) barriers in implementing religious education policies, (2) the impact on students of indigenous beliefs, and (3) best practices from schools that accommodate their religious education. Using the PRISMA approach, data was gathered through a systematic review of educational regulations, previous research, and online sources like Google Scholar, Scopus, and PubMed. The study identifies three main barriers: juridical, philosophical, and social. These barriers negatively impact students psychologically, causing difficulties in acceptance, trauma, fear, and the need for social advocacy. However, some schools have successfully implemented inclusive education by allowing indigenous belief students to receive religious and moral education according to their faith. These schools foster a tolerant environment, support religious freedom, and promote diversity awareness among students and educators. Their approach can serve as a model for other schools struggling to accommodate indigenous belief students.